Factors affecting stock prices in the capital market - Putri, Syifa Aulia Zhara (Maliki Interdisciplinary Journal, 2024)
Stock prices are important for an investor to know before buying shares in the capital market. A better understanding of the factors that affect stock prices can help them make more informed and effective investment decisions. In addition, this research can also provide valuable insights in designing better investment strategies and anticipating future stock price movements. This article aims to analyze the factors that affect a company’s stock price. Through a review of the literature and previous studies in finance, several factors have strong potential to influence stock prices. These factors include the company’s financial performance, interest rates, market sentiment, macroeconomic conditions, industry competition, dividend policy, global market conditions, and government policies. The results of this study have important implications for investors, financial analysts and decision makers in financial markets